Implementation of customer relationship management in building library users' loyalty - Silvana, Hana; Hermansyah, Rosika Pertiwi (Universitas Padjadjaran, 2024)
Customer Relations Management (CRM) is an effort made to build and maintain relationships between libraries and their users to meet the needs and increase satisfaction of library users. It is carried out to realize excellent service in a library, which leads to creating user loyalty to continue using all the facilities provided by the library. The purpose of this study was to describe how the Universitas Pendidikan Indonesia (UPI) Library implemented CRM to meet needs and create user satisfaction to increase user loyalty. This study used a qualitative approach with a descriptive method thorugh interviews and observation with four informants. The results of the study showed that the application of CRM at UPI Library in increasing customer loyalty includes three factors, namely carrying out various efforts to get new customers (Acquire), making efforts to improve relationships with existing customers (Enhance), and making efforts to retain customers (Retain). The approach to achieving these three goals was to deliver exceptional service by refining current offerings and developing new ones that were in step with technology advancements. Fulfilling the needs of users will provide satisfaction for them, which in the end can build a positive image of users towards the library and establish a good relationship between users and the library to create a loyal community.